C and K band microwave penetration into snow on sea ice studied with off-the-shelf tank radars - Jutila, Arttu; Haas, Christian (International Glaciological Society., 2023)
Snow cover on sea ice poses a challenge for radar measurements as microwave penetration into snow is not yet fully understood. In this study, the aim is to investigate microwave penetration into snow on Arctic sea ice using commercial C (6 GHz) and K (26 GHz) band tank radars. Nadir-looking radar measurements collected at nine study locations over first-year and multiyear landfast sea ice in the Lincoln Sea in May 2018 are analysed together with detailed measurements of the physical properties of the snow cover to determine the dominant scattering horizons at both frequencies. They are evaluated for the feasibility to determine snow depth. The results show that in 39% of the measurements and only on first-year ice a major fraction of the C band radar backscatter originated closer to the snow–ice interface potentially enabling snow depth retrieval. At K band, 81% of the radar returns originated from the snow surface. Partly confirming the findings of previous studies, however, the analysis was potentially hampered by relatively warm air temperatures (up to −0.9◦C) during the study period as well as stratigraphic features and inconclusive microwave interaction with the saline basal layers found in the snow cover on first-year ice.